(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
B. insularis is recorded as further instance of ovoviviparous species in the subf. ldolothripinae. Evidence for its reproductive behaviour arose by dissecting many females collected from June to October. Moreover, some females were kept alive in vials to observe oviposition. Abundant material, including adults and neanides of this thrips, was selected from samples of Bermuda grass stems, collected in different localities of southern Italy. Out of some 60 females dissected throughout, 21 egg-bearing items were observed. Eggs were in a number ranging from 1 to 14 in each female and completely developed in a large rate; they were stored in a dilated tract of female genitalia, which does evidently correspond to the usual oviducts of other thrips. Observations on live females showed that eggs do hatch within few hours after they have been released. Altogether, results assert that females of B. insularis are used to incubate eggs up to the complete development. Because it lacks special maternal nutrition structures for embryos, this thrips must be formally classified as ovoviviparous (not viviparous) according to Engelmann’s terminology (1970).